(untitled) (Materiali di Estetica. Terza serie, 2022)
Art is a necessary aspect of existence, as Nietzsche puts it so beautifully: "Art makes life conceivable and worthy of living.” (F. Nietzsche, The Birth of Tragedy, trad. W. Kaufmann, New York, 1967). Otherwise, it leads to a crisis known as "disability," which includes the incapacity to comprehend, perform, and present. As Nietzsche compares the artist to Hamlet in his book, the artist is shown to be capable of achieving nothing, and his incapacity stems from the fact that there is no longer any link between knowledge and action, and therefore even Dionysus happiness, It makes no difference in the world. The root of this incompetence is a critical issue that must be addressed in order to solve art-related issues